(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
It has been widely studied recent as well as historic accumulation of elements in peat profiles depending on intensity of anthropogenic pollution and thereby peat profiles serve as archives for research of environmental change. Peat ability to accumulate major and trace elements depends on the character of element supply, potency of metal ions to bind functionalities in the peat structure, pH reaction, oxygen presence, presence of complexing compounds, inorganic ions and many other factors. The aim of this study is to assign major and trace element distribution in humic acids (HA) for two well characterized ombrotrophic peat profiles of Eipurs and Dzelve Bog and analyse factors affecting element concentration in peat humic acids. Elemental and functional analysis of the isolated HAs was done, using total reflection X – ray spectrometry, Elemental Analyzer Model EA – 1108, Thermospectronic Helios γ UV (Thermo Electron Co.) spectrophotometer, Total acidity method.